Common variants in MMP20 at 11q22.2 predispose to 11q deletion and neuroblastoma risk - Xiao Chang (Nature Portfolio, 2017)
Chromosomal abnormalities such as 11q deletion are associated with poor prognosis in neuroblastoma. Here, the authors perform a genome-wide association study and identify an association between a variant within a Matrix metalloproteinase (MMP) gene member, MMP20, and 11q-deletion subtype neuroblastoma.